Produtividade do tifton 85 (Cynodon spp.) em função do uso de fertilizantes organominerais e reguladores de crescimento - Schneider, Joemir Egidio (My University, 2021)
The interest in increasing the productivity of cultivated pastures requires the implementation of tools that provide increments in terms of green mass and pasture quality. The objective was to evaluate the response of Tifton 85 pasture under the effect of different types of fertilization. The experiment was carried out on a rural property located in the district of Piedade, Municipality of São Vendelino/RS. The experimental period covered the months of October 2020 to May 2021, with an evaluation period of 21/21 days. The first collection took place with the pasture fully established, 100 days after planting the seedlings. Six treatments were tested: TT0: Witness Treatment; TT+: Positive control treatment; TB: Biosolli Treatment; TB+: Biosolli + conventional treatment; TA: Additive Treatment; TA+: Additive + conventional treatment. The experimental design was in randomized blocks, with four replications of each treatment (Experimental unit: 3mx4m plot). The variables evaluated were: dry matter production per hectare, regrowth potential, percentage levels of crude protein and neutral detergent fiber. Data were subjected to analysis of variance (ANOVA), and means compared by Tukey test (5%), using the statistical program AgroEstat. The production of dry matter per hectare and the height of the pasture were significantly influenced (p<0.05) by the treatment, with TB+, followed by TT+ and TB being the ones with the highest productivity. The percentages of neutral detergent fiber and crude protein were significantly influenced (p<0.05) by treatments and showed significant interaction (p<0.05) between treatments and cutting period. The use of basic conventional fertilization, with or without foliar fertilization with Biosolli, tends to increase productivity, however, due to the excellent soil fertility in the experiment, the ideal would be to continue with more cuts, to intensify the evaluations in the more mature stages forage and thus identify a more expressive effect of the treatments. [resumo fornecido pelo autor]
O interesse em aumentar a produtividade das pastagens cultivadas, exige a implementação de ferramentas que proporcionem incrementos em termos de massa verde e qualidade das pastagens. Objetivou-se avaliar a resposta da pastagem de Tifton 85 sob efeito de diferentes tipos de fertilização. O experimento foi realizado na propriedade rural no Município de São Vendelino/RS. O período experimental compreendeu os meses de outubro de 2020 a maio de 2021, com periodicidade de avaliação de 21/21 dias. A primeira coleta ocorreu com a pastagem totalmente estabelecida, 100 dias após o plantio das mudas. Foram testados seis tratamentos: TT0: Tratamento Testemunha; TT+: Tratamento testemunha positiva; TB: Tratamento Biosolli; TB+: Tratamento Biosolli + convencional; TA: Tratamento Additive; TA+: Tratamento Additive + convencional. O delineamento experimental foi em blocos casualizados, com seis repetições de cada tratamento. As variáveis avaliadas foram: produção de matéria seca por hectare, níveis percentuais de proteína bruta e fibra em detergente neutro. Os dados foram submetidos à análise de variância (ANOVA), e as médias comparadas pelo teste de Tukey (5%), por meio do programa estatístico AgroEstat. A produção de matéria seca por hectare e a altura da pastagem foram influenciadas significativamente (p<0,05) pelo tratamento, sendo os TB+, seguido pelo TT+ e TB os de maior produtividade. Os percentuais de fibra em detergente neutro e proteína bruta foram influenciados significativamente (p<0,05) pelos tratamentos e apresentaram interação significativa (p<0,05) entre tratamentos e período de corte. A proteína bruta apresentou valores maiores e o FDN consequentemente menor, ou seja, maior digestibilidade. O uso de adubação convencional de base, acrescida ou não de adubação foliar com Biosolli, apresenta a tendência a maior produtividade, entretanto, pela excelente fertilidade do solo no experimento, o ideal seria seguir com mais cortes, para intensificar as avaliações nos estádios mais maduros da forragem e assim, identificar um efeito mais expressivo dos tratamentos. [resumo fornecido pelo autor]
Keywords: Agronomia; Pastagens - Manejo; Adubos e fertilizantes; Aditivos